The global workplace : international and comparative employment law : cases and materials / Roger Blanpain [and four others]. - Blanpain, R. (Roger), 1932- (Cambridge University Press, 2007)
With the forces of globalization as a backdrop, this casebook develops labor and employment law in the context of the national laws of nine countries important to the global economy - the US, Canada, Mexico, UK, Germany, France, China, Japan and India. These national jurisdictions are highlighted by considering international labor standards promulgated by the International Labor Organization as well as the rulings and standards that emerge from two very different regional trade arrangements - the labor side accord to NAFTA and the European Union. Across all these different sources of law, this book considers the law of individual employment, collective labor law dealing with unionization as well as the laws against discrimination, the laws protecting privacy and the systems used to resolve labor and employment disputes. This is the first set of law school course materials in English covering international and comparative employment and labor law.